Improving sociocultural adaptation of first-year Chinese international undergraduate students: Peer mentorship and intercultural engagement - Ma, Lan (Journal of International Students, 2026)
This action research explored ways to enhance the sociocultural adaptation of first-year Chinese international undergraduates at a private research university in the midwestern U.S. through peer mentorship and intercultural engagement. Cycle 1 of the study identified social and cultural challenges, such as forming intercultural relationships, leading to a heavy reliance on conational networks for adjustment and adaptation. In response, Cycle 2 introduced a four-part pilot program: the Chinese Student Mentorship Program, the Academic Peer Mentorship Program, the International Ambassadors Program, and the Residential Community Engagement Program. Using the Revised Sociocultural Adaptation Scale (SCAS-R), a post-program survey, and semistructured interviews, the study revealed improved SCAS-R scores and confirmed the effectiveness of peer mentorship and residential engagement in supporting daily life, academic transitions, and social connections.